Digital Literacy in Islamic Elementary Schools: an Overview of The Factors, Challenges, and Impact 21st Century Skills Development - Nisa, Rofiatun (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to explore the key factors, challenges, and impacts of digital literacy implementation in Islamic elementary schools, particularly regarding the development of 21st-century skills. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, a total of 41 relevant articles from the Scopus database (2015–2024) were analyzed. The findings reveal that digital literacy in Madrasah Ibtidaiyah is influenced by several interconnected elements, including technological infrastructure, government policies, teacher competence, and parental roles. The study also identifies significant challenges, such as limited access to technology, uneven teacher preparedness, and socio-cultural resistance, especially in rural and under-resourced areas. Despite these barriers, the implementation of digital literacy has shown a positive impact on students’ abilities in critical thinking, collaboration, problem-solving, and digital communication, when framed within Islamic educational values. These results underscore the need for integrative and faith-based approaches to digital literacy in order to support both technological competency and moral development in Islamic primary education.